2021
DOI: 10.3389/fncel.2021.695817
|View full text |Cite
|
Sign up to set email alerts
|

Astrocytic IP3Rs: Beyond IP3R2

Abstract: Astrocytes are sensitive to ongoing neuronal/network activities and, accordingly, regulate neuronal functions (synaptic transmission, synaptic plasticity, behavior, etc.) by the context-dependent release of several gliotransmitters (e.g., glutamate, glycine, D-serine, ATP). To sense diverse input, astrocytes express a plethora of G-protein coupled receptors, which couple, via Gi/o and Gq, to the intracellular Ca2+ release channel IP3-receptor (IP3R). Indeed, manipulating astrocytic IP3R-Ca2+ signaling is highl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 157 publications
(233 reference statements)
1
34
0
Order By: Relevance
“…Furthermore, the model used in this study, focusing on the effect of the ER shape and distribution on Ca 2+ activity, describes with great details the kinetics of ER-mediated Ca 2+ signals while simplifying other Ca 2+ sources. Other Ca 2+ sources and channels however contribute to Ca 2+ microdomain activity in PAPs, including mitochondria, the Na + /Ca 2+ exchanger, transient receptor potential ankyrin 1 channels, L-type voltage gated channels and other pathways ( 27 , 43 ). According to our model’s predictions, the spatial distribution of Ca 2+ channels can alter the spatio-temporal properties of Ca 2+ microdomain signals in PAPs as well as their amplification upon neuronal stimulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the model used in this study, focusing on the effect of the ER shape and distribution on Ca 2+ activity, describes with great details the kinetics of ER-mediated Ca 2+ signals while simplifying other Ca 2+ sources. Other Ca 2+ sources and channels however contribute to Ca 2+ microdomain activity in PAPs, including mitochondria, the Na + /Ca 2+ exchanger, transient receptor potential ankyrin 1 channels, L-type voltage gated channels and other pathways ( 27 , 43 ). According to our model’s predictions, the spatial distribution of Ca 2+ channels can alter the spatio-temporal properties of Ca 2+ microdomain signals in PAPs as well as their amplification upon neuronal stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…mGluR activation on the astrocytic membrane following neurotransmission at glutamatergic synapses results in Ca 2+ transients mediated by G q proteins and Ca 2+ stores such as the endoplasmic reticulum (ER) [64], which can trigger the release of molecules that modulate neurotransmission, referred to as gliotransmitters[15, 48, 3, 60]. Most astrocytic Ca 2+ signals are mediated by the Inositol 3-Phosphate (IP 3 ) receptors on the membrane of the endoplasmic reticulum (ER) [62]. Because of their nanoscopic size, the Ca 2+ pathways involved in microdomain Ca 2+ signals in PAPs are still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…enhanced mEPSPs in surrounding neurons [ 61 ]. Noteworthy, peripheral astrocytic processes (PAPs) are critically involved in synaptic plasticity and are known to display spotty Ca 2+ transients in their microdomains [ 27 , 62 , 63 ]. Although no elevations in Ca 2+ transients were observed in our study, assessment of Ca 2+ transients was restricted to the soma and large processes, as Ca 2+ -imaging was performed using two-photon Ca 2+ imaging after bolus loading of a chemical dye (OGB-1 AM), which is known to have limited spatial resolution [ 64 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although astrocytic IP3R2 expression is required for certain mechanisms of LTD formation, the genetic defects in IP3R2 are not sufficient to fully prevent LTP generation what probably reflects astrocyte diversity in different brain regions (Oberheim et al, 2012 ). Recently, it has been suggested that IP3R1 and IP3R3 subtypes co-exist in astroglia and retain their functionality by generating local Ca 2+ events (Sherwood et al, 2017 , 2021 ). The second key type of Ca 2+ -permeable receptor channel in the ER is the ryanodine receptor (RyR) but the mechanism of its activation and inhibition by Ca 2+ remains largely unexplored and controversial (Rodríguez-Prados et al, 2020 ; Skowrońska et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%